Research on the Effects of Supercritical Water /CO2 Mixed Environment on Biomass - Zhang, Lei; Jiang, Zaichao; Wang, Yulong (Scientific Journal of Technology, 2025)
The supercritical water/CO₂ mixed environment, through its unique physicochemical properties and synergistic effects, not only enables the decomposition of biomass but also the generation of energy gases and the capture of CO2, demonstrating a significant role in energy and high-value conversion. This paper studies the reactions of different biomass in a supercritical water /CO2 mixed environment, systematically compares and analyzes the reaction results of various biomass, and ultimately concludes that CO2 has the functions of improving thermal efficiency, hydrogen production and carbon sequestration in the supercritical water process.